Comunicação, consumo e memória: a construção da memória religiosa na página Otaku Cristão - Moreira, Flavio Salcedo Rodrigues (2019)
The digital media provide the circulation of various cultural texts between different memory systems. From the consumption of these texts, individuals and social groups organize their practices and social structures. In this interaction between distinct cultural systems, some texts end up being absorbed or re-signified, generating new memories, social practices, value systems and beliefs that can be considered in some way hybrids derived from these encounters at cultural borders. An example of this is what occurs in the production of cultural texts from the Otaku Christian Facebook page, the empirical object of this dissertation. Present in his productions are two distinct systems of memories: Japanese pop culture and evangelical Christian religious culture. The postings made on the page do not only reflect the media consumption tastes of its producers, but reflect the possibilities of interaction and re - signification of the memes - values - coming from each culture system involved. Therefore, to analyze the productions of the Christian Otaku page this work has as a research problem the following question: How does the production and consumption of Japanese pop culture cultural texts present on the Otaku Christian page work in the formation of the religious memory of young evangelicals? The general objective is to understand how the production and consumption of cultural texts work in the construction of the religious memory articulated by the Otaku Christian page. The specific objectives are: 1) To analyze the process of producing cultural texts on the Otaku Christian page in publications containing images of Japanese pop culture superimposed on biblical texts; 2) Observe how the consumption of cultural texts of Japanese pop culture act in the organization and production of religious memories of young evangelicals. As theoretical bases for the understanding and analysis of this phenomenon, this work is organized in two major epistemic nuclei. The first one is about the media consumption, having as main authors Roger Silverstone (2014), Stig Hjarvard (2014), Lúcia Santaella (2013) and Monica R. F. Nunes (2001, 2015). The second core covers the concepts of memory, culture and religion, and its key authors Iuri Lotmann (1984, 1996, 2001, 2009), Monica RF Nunes (1993, 2001, 2015), Richard Dawkins (2006), Yuzuru Tanaka Soares (2003), Maurice Halbwachs (2013), Mircea Eliade (1978), Aleida Assmann (2008, 2011) and Jan Assmann (1995, 2008a). The delimitation of the material to be analyzed was based on two criteria: the first is a qualitative delimitation in which cultural texts were sought that were composed by an image of a product of Japanese pop culture and a biblical verse. The second is a quantitative delimitation in which the compound week method was used to select 14 images. As expected results, it was verified, among other points, that the cultural texts on the page act as organizers of social practices and also as a reinforcement of identity for those who consume them. In addition, it was possible to visualize that those who identify themselves as a Christian otaku are individuals who circulate between the frontiers of pop culture and the evangelical religion, organizing their religious memories from the media symbols of Japanese pop culture.